Studies on Medieval Turkish and Islamic Naval History in Türkiye on the 100th Anniversary of The Turkish Republic - Murat Öztürk (Tarih Dergisi)
The study of Turkish maritime history in the Middle Ages, which is thought by some historians to have begun in 395 when the Roman Empire was divided into East and West and ended with the conquest of Constantinople on May 29, 1453, began in the republican era and the number of studies on both Turkish and Islamic maritime history has continued to increase gradually over time. However, unfortunately, due to the difficulties of conducting academic research in this field, there is a paucity of scientific studies on medieval maritime history. In this article, the maritime activities of the Turkish and Islamic states in the Middle Ages, which are important in political, military, and economic contexts, and the events that took place at sea are discussed and evaluated, and the studies and translations that contributed to the field in Türkiye in the 100 years, namely from 1923 to 2023, are included.